2021
DOI: 10.3389/fphys.2021.703281
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Hypoxia Reduces the Effects of Glucosteroid in Asthma via Activating the p38 MAPK Signaling Pathway

Abstract: AimsObstructive sleep apnea (OSA) is a risk factor for steroid-resistant (SR) asthma. However, the underlying mechanism is not well defined. This study aimed to investigate how chronic intermittent hypoxia (CIH), the main pathophysiology of OSA, influenced the effects of glucocorticoids (GCs) on asthma.Main MethodsThe effects of dexamethasone (Dex) were determined using the ovalbumin (OVA)-challenged mouse model of asthma and transforming growth factor (TGF)-β treated airway smooth muscle cells (ASMCs), with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…7 Schisandrin B could also attenuate airway inflammation by mediating the NF-κB pathway in asthma animal model. 17 These studies confirmed that this pathway could serve as a promising target for asthma.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…7 Schisandrin B could also attenuate airway inflammation by mediating the NF-κB pathway in asthma animal model. 17 These studies confirmed that this pathway could serve as a promising target for asthma.…”
Section: Discussionmentioning
confidence: 63%
“…NF-κB signaling plays an important role in regulating proinflammatory cytokines production, and recruiting eosinophils, which promotes allergic inflammation. 17 Activation of NF-κB pathway has been implicated in allergic asthma. To reveal the potential mechanism, the activation of NF-κB signaling pathway was analyzed (Figure 4).…”
Section: Scopoletin Inhibits Proliferation and Invasion Of Asmcs By Regulating Nf-κb Signaling Pathwaymentioning
confidence: 99%
“…Other authors demonstrated that chronic intermittent hypoxia (CIH) led to bronchial hyperreactivity, increased airway and systemic inflammation, and thus promoted the risk of refractory asthma [ 18 ]. In addition, according to the studies, treatment with p38 MAPK inhibitor substantially decreased the inflammation scores in an asthma mice model [ 8 ]. Also, CIH decreased the glucosteroid sensitivity by activating the p38 MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ERK and JNK phosphorylation and activation also can be affected after stimulation with glucosteroids, although the mechanism of this regulation is not fully elucidated [ 19 ]. Other studies have shown that CIH exposure led to the activation of the p38 MAPK pathway in the nervous system and vascular endothelium [ 8 ]. From this point of view, our study also showed that IH induced ERK and p38 MAPK activation by phosphorylation, at the same time with no significant changes in JNK phosphorylation, even though the results show downregulation of MEK phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation